210 RECTAL CARCINOIDS: A SINGLE-CENTER EXPERIENCE. Issue 1 (1st January 2007) - Smith, R. D.; Sachdev, M. S.; Tombazzi, C.; Ismail, M. K.
Abstract : Background: Rectal carcinoids are considered to be neuroendocrine tumors and usually present as a single solitary submucosal nodule. Our study aimed to evaluate the presentation, management, and outcome of all rectal carcinoids diagnosed at our institution. Methods: A retrospective review of endoscopic and pathologic databases was undertaken to identify all cases of rectal carcinoids. Medical records were reviewed for clinical, endoscopic, and surgical treatment. A median follow-up of 26 months (range 1-132 months) was available. Results: Eighteen patients with a median age of 59 years (range 34-80 years) were identified with a diagnosis of rectal carcinoid over 14 years (11/91 to 12/05). All were male and 14 of 18 patients were African American. All patients were asymptomatic, except for one with a rectal lesion and hepatic metastasis. All lesions were identified incidentally during endoscopic examination with the exception of two patients (one with hepatic metastasis and another incidentally noted after surgical resection of rectal adenocarcinoma). On endoscopic examination, rectal carcinoid appeared as yellow/gray or tan submucosal nodules with sizes ranging from 3 to 12 mm, except in one patient with a rectal mass measuring 45 mm. Only two patients underwent an endoscopic ultrasound examination, which revealed lesions limited to the submucosa. Sixteen patients underwent endoscopic resection (hot biopsy/polypectomy with saline injection-band ligation technique). One patient underwent surgery (with positive margins following endoscopic resection). One patient had hepatic metastasis and did not undergo any further therapy. Follow-up endoscopic examination with biopsy for recurrence was negative in 12 patients who underwent follow-up endoscopic examination. During the follow-up three patients died, two of whom as a result of carcinoid. Conclusion: Incidental finding of rectal carcinoids was not an uncommon occurrence. The majority of these lesions were seen among African American males. Endoscopic resection of small carcinoid tumors is usually successful, without any local recurrence. Prospective studies are needed to confirm the findings and role of endoscopic ultrasonography in guiding endoscopic resection of rectal carcinoid.